The effect of preexisting HMGB1 within fetal bovine serum on murine pancreatic beta cell biology. Issue 1 (2nd January 2020) - Chung, Hyunwoo; Hong, Sung Ji; Choi, So Won; Park, Chung-Gyu
ABSTRACT: High-mobility group box 1 (HMGB1) can act as a structural protein of the chromatin and at the same time as a mediator of the immune system. Its high correlation with the graft acceptance in pancreatic islet recipients makes it a biomarker in islet transplantation. With the suspicion that preexisting HMGB1 in the fetal bovine serum (FBS) would be detrimental to the viability and function of murine beta cells, HMGB1 was removed from FBS and its impact was investigated. Interestingly, the elimination of HMGB1 from FBS seemed unfavorable to the viability and function of cultured murine beta cells, suggesting that the preexisting HMGB1 in the FBS may be an indispensable component of islet cell culture.